Evaluating greenhouse gas emissions and carbon credit potential of solid waste disposal facilities: the case of Istanbul - Aydin, C.; Akkaya, E. Koca (SPRINGER, 2025)
Increasing population and urbanization across the world are rapidly increasing waste generation, which in turn contributes significantly to global greenhouse gas emissions. In the fight against climate change, technology is important for reducing waste emissions. Hence, in this study, greenhouse gas emissions and carbon credit values of municipal solid waste (MSW) disposal facilities such as sanitary landfill, waste incineration and biogas facilities in Istanbul are analyzed for the year of 2023, using real facility data based on IPCC and Gold Standard methodologies. The results obtained are comprehensively evaluated with the related literature studies. The annual non-biogenic emissions per t of waste were found to be: 0.461 tCO2e for Kemerburgaz waste incineration; 0.457 tCO2e for Seymen LFG and 0.001 tCO2e for Kemerburgaz biogas. In addition, it is determined that the waste incineration facility has the highest carbon credit amount with 1,469,676 tCO(2)e. Carbon reduction of 1,257,087 tCO(2)e is achieved in the sanitary landfill facility and 16,340 tCO(2)e in the biogas facility. Energy generation per t of waste was also highest in the incineration facility (0.59 MWh), compared to the biogas facility (0.19 MWh) and LFG facility (0.09 MWh). As a result, this study provides contribution to the development of sustainable waste management strategies, reduction of greenhouse gas emissions and evaluation of carbon credit potentials and to be a reference source in related fields.
Keywords: Carbon offset; Climate impact; Renewable energy; Sustainability; Waste management; Waste to energy; MANAGEMENT; Environmental Sciences & Ecology